Uncertain Times: Clinical Decision-Making in Sickness and in Health - Laura Willett (Association of American Medical Colleges, 2013)
Abstract Introduction It is increasingly important for medical students to recognize the importance of uncertainty in clinical decision-making. At our institution we implemented a three-part session at the beginning of second-year medical school, prior to organ system-based blocks incorporating traditional pathophysiology, pathology, and pharmacology. Methods This three-module set begins with one introductory lecture followed by two team-based learning sessions. The content focuses on the basics of diagnostic and therapeutic decision-making with a major emphasis is on pre- and posttesting probabilities. Results This fairly new course has been received with enthusiasm by our medical students, who have responded with very high marks (4 out of 5) for the last 3 years and with comments such as, "I finally understand probability after all these years." Discussion While this resource is a good start, it is probably not enough to cement these concepts without later reinforcement. We are planning to put some predictive value modules into case sessions later in the second year, such as testing for adrenal insufficiency during the endocrine block. While we implement it with second-year medical students, it could be used for learners at many different levels with minor changes.